Atractylenolide I Inhibits NLRP3 Inflammasome Activation in Colitis-Associated Colorectal Cancer via Suppressing Drp1-Mediated Mitochondrial Fission - Qin, Yao; Yu, Yanwei; Yang, Chendong; Wang, Zhuien; Yang, Yi; Wang, Chongxu; Zheng, Qiusheng; Li, Defang; Xu, Wenjuan (Frontiers in Pharmacology, 2021)
Inflammatory bowel disease (IBD) is a high-risk factor for colon cancer. Regulation of NLRP3 provides an interesting mechanism to change the inflammatory potential of immune cells and provides a potential target for the treatment of NLRP3 inflammasomes-related diseases. In this study, the effects of Atractylenolide I on azoxymethane (AOM) and dextran sodium sulfate (DSS) induced colitis associated CRC (caCRC) and inflammasome activation were investigated both in vivo and in vitro. In addition, the role of Atractylenolide I on Drp1-mediated mitochondrial fission was analyzed via western blotting and Transmission electron microscopy (TEM). Moreover, Drp1 overexpression lentiviral vector was used to study the role of Drp1 on the signaling mechanisms of Atractylenolide I. Atractylenolide I treatment notably reduced cell viability and induced apoptosis in human HCT116 and SW480 cells, and effectively suppressed colonic neoplasms in AOM/DSS mice model. The decrease of NLRP3 inflammasomes activation and excessive fission of mitochondria mediated by Drp1 was associated with Atractylenolide I administration. The inhibitory effect of Atractylenolide I on NLRP3 inflammasomes activation was reversed by upregulating Drp1. Overexpressing Drp1 expression counteracted the restraint of Atractylenolide I on the release of IL-1β of LPS/DSS-stimulated BMDMs. Atractylenolide I treatment greatly inhibited NLRP3 and Caspase-1 expression at the protein level in mice BMDMs, with no influence on NLRP3 and Caspase-1 expression in the Drp1-overexpression BMDMs. These results demonstrated that Atractylenolide I inhibits NLRP3 inflammasomes activation in colitis associated colorectal cancer via suppressing Drp1-mediated mitochondrial fission.